Integrated hydrogeophysical and GIS based demarcation of groundwater potential and vulnerability zones in a hard rock and sedimentary terrain of Southern India. (March 2023) - Sankar, K.; Karunanidhi, D.; Kalaivanan, K.; Subramani, T.; Shanthi, D.; Balamurugan, P.
Abstract: This research has identified the groundwater potential and vulnerability zones in Tiruchirappalli district of Tamil Nadu, India. The Schlumberger electrode array has been used to conduct vertical electrical sounding (VES) at 95 sites with a maximum electrode spacing of 150 m. The study area comprises of hard rock and sedimentary formations. Geographical Information System (GIS) has been used to integrate the geoelectrical data and to prepare spatial variation maps for various parameters. Finally, groundwater potential and vulnerability zones have been demarcated, and these outputs have been validated using water level and nitrate data, respectively. The Dar-Zarrouk parameters such as longitudinal conductance (S), transverse unit resistance (T), and aquifer anisotropy (λ) have been used along with the spatial variation of resistivity and aquifer thickness to find out groundwater potential areas with the support of GIS. The thickness of topsoil, weathered zone and fractured zone are not uniform in the research area. Top soil plus weathered zone acts as a water table (phreatic) aquifer, which extends up to 38 m from the surface. Fractured zone extends up to 45 m, which acts as a kind of confined/semi-confined aquifer. Open and bore wells have been constructed to tap groundwater from the unconfined (water table) and confined/semi-confined aquifers, respectively. High to very high groundwater potential areas are associated with low resistivity, high thickness, low longitudinal conductance, high transverse unit resistance and high aquifer anisotropy areas. Very high groundwater potential areas are mostly confined to flood plain (alluvium) deposits in the central portion of the study area. High potential areas are noticed in the northern part, whereas low potential areas are noticed in the southern part. The areas with high longitudinal conductance indicate low permeable zones with less possibility of external pollution. Since agriculture is an important activity in the study region, this work will be useful to provide water supply for irrigation as well as for domestic needs. Graphical abstract: Image 1 Highlights: IPI2Win was used for curve matching to evaluate VES data obtained from 95 locations. Spatial variations of thickness of top soil, weathered zone and fractured zone were plotted using GIS. Thickness of weathered zone varied from <10 m to >38 m, which played a major role in groundwater occurrence. Groundwater potential zones were demarcated using hydrogeophysical investigations.